The Effect of Edm Die-sinking Parameters on Material Removal Rate of Beryllium Copper Using Full Factorial Method - Md Ali, Mohd Amran; M., Samsul; HUSSEIN, NUR IZAN SYAHRIAH; Mohd Rizal , Salleh; Raja Izamshah , Raja Abdullah; Mohd , Hadzley; Mohd Shahir, Kasim; Mohd Amri , Sulaiman; Sivarao, Subramonian (2013)
The effect of electrical discharge machining (EDM) die-sinking parameters on material removal rate (MRR) of Beryllium Copper (BeCu) was studied. EDM die-sinking is one of the important non-traditional machining processes and it is widely accepted as a standard machining process in the manufacturing of forming tools to produce mould and die. The appropriate parameters were selected to study the influence of operating parameters of BeCu on MRR. Electrolytic copper was selected as electrode with positive polarity. The experiment was done using SODICK AQ35L EDM machine. Two level approach of full factorial design of experiment was applied to design the experimental and the data was analyzed by using analysis of variance (ANOVA) and the optimal combinations of the process parameters were predicted. It is found that peak current was the most significant factor affecting the MRR. Further, pulse on time and pulse off time must be combined with other factors in order to influence the machining characteristics. Finally, machine voltage shows less significant factor for the EDM die-sinking process on BeCu.